2020
DOI: 10.3390/ijms21020518
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of GABAA-A1R Developmental Alterations in Rett Syndrome: Setting the Focus for Therapeutic Targets in the Time Frame of the Disease

Abstract: Rett syndrome, a serious neurodevelopmental disorder, has been associated with an altered expression of different synaptic-related proteins and aberrant glutamatergic and γ-aminobutyric acid (GABA)ergic neurotransmission. Despite its severity, it lacks a therapeutic option. Through this work we aimed to define the relationship between MeCP2 and GABAA.-A1 receptor expression, emphasizing the time dependence of such relationship. For this, we analyzed the expression of the ionotropic receptor subunit in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…Combined with the result of the present work, these data indicate that, at least in the Mecp2 −/y CA3 pyramidal neurons, the GABAergic developmental sequence is delayed at pre-symptomatic stages and restored at symptomatic stages. Interestingly, a recent study reported that the expression of KCC2 is downregulated in cortices of presymptomatic but not symptomatic female Mecp2 −/+ mice (Oyarzabal et al, 2020), further suggesting that a transient alteration of GABAergic inhibition takes place in this RTT mouse model. Disruptions of the GABAergic developmental sequence have been reported to alter the trajectory of brain development, hence functioning in adulthood.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Combined with the result of the present work, these data indicate that, at least in the Mecp2 −/y CA3 pyramidal neurons, the GABAergic developmental sequence is delayed at pre-symptomatic stages and restored at symptomatic stages. Interestingly, a recent study reported that the expression of KCC2 is downregulated in cortices of presymptomatic but not symptomatic female Mecp2 −/+ mice (Oyarzabal et al, 2020), further suggesting that a transient alteration of GABAergic inhibition takes place in this RTT mouse model. Disruptions of the GABAergic developmental sequence have been reported to alter the trajectory of brain development, hence functioning in adulthood.…”
Section: Discussionmentioning
confidence: 84%
“…A decrease of KCC2 expression and impaired chloride homeostasis was also reported in the visual cortex (Banerjee et al, 2016;Scaramuzza et al, 2021) and hippocampus (El-Khoury et al, 2014;Lozovaya et al, 2019) of Mecp2-null mice. However, most of these investigations were performed at stages when the symptoms are not overt (Banerjee et al, 2016;Lozovaya et al, 2019;Scaramuzza et al, 2021), and whether these alterations persist to late symptomatic stages has been recently questioned (Oyarzabal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…MeCP2-null mice exhibited increased amplitude of spontaneous miniature and evoked excitatory postsynaptic current (EPSC)s without affecting the intrinsic excitability in the nucleus tractus solitarius (NTS), which is associated with decreased brainderived neurotrophic factor (BDNF) availability in the primary afferent pathway, and these changes can be normalized by exogenous BDNF application (Kline et al, 2010). Some evidence has demonstrated that the loss of MeCP2 induces reduced expression levels of vesicular GABA transporter (VGAT), GAD1, and GAD2, and altered expression of GABA-AR subunits (Medrihan et al, 2008;Chao et al, 2010;Chen et al, 2018;Oyarzabal et al, 2020). In particular, it was found that GABA-A subunit expression was developmentally decreased especially in the no-symptom stage in MeCP2+/− mouse brain (Oyarzabal et al, 2020).…”
Section: Mecp2mentioning
confidence: 99%
“…In an in vitro study, MeCP2 expression activated the expression of the GABA A R α1 subunit [53]. The regulation of multiple GABA A R subunit expression patterns in tissue from Rett patients as well as models suggest that MeCP2 may be a global transcriptional regulator of GABA A R subunit genes [53]. Epigenetic regulation induced via the phosphorylation of MeCP2 has recently been implicated in the gene expression changes that follow exposure to substances [54].…”
Section: Transcriptionmentioning
confidence: 99%
“…In addition, it has been shown that the α 1 subunit is downregulated in the frontal cortex, while α 2 and α 4 are reduced in the ventrolateral medulla of the MeCP2-null model [ 51 , 52 ]. In an in vitro study, MeCP2 expression activated the expression of the GABA A R α1 subunit [ 53 ]. The regulation of multiple GABA A R subunit expression patterns in tissue from Rett patients as well as models suggest that MeCP2 may be a global transcriptional regulator of GABA A R subunit genes [ 53 ].…”
Section: Basal Mechanisms Regulating Gaba a Recmentioning
confidence: 99%